Metal-Free Amidation and Selenoamidation of 2-Methylquinolines with Secondary Amines Using Selenium Dioxide, and Antibacterial Evaluation of the Products - Shaikh, Arbaz Sujat; Rathod, Mahipal Singh; Vemula, Divya; Makhal, Priyanka N.; Bhandhari, Vasundhara; Kaki, Venkata Rao (Synlett, 2025)
We report a metal-free protocol for the amidation and selenoamidation of 2-methylquinolines by using selenium dioxide as the key reagent. This method offers several advantages, including ease of operation, a short reaction time (15 min), and moderate to excellent yields (50–90%). The method demonstrates a broad substrate tolerance, including various secondary amines and 2-methyl heterocycles such as pyridine and benzothiazole. The applicability of the method was further highlighted through late-stage functionalization of ciprofloxacin, yielding a bioactive hybrid molecule with a remarkable MIC value of 0.195 μg/mL.
Keywords: methylquinolines; amidation; selenoamidation; selenium dioxide; metal-free reaction